INSTRUCTIONAL APPROACHES IN VISUAL ARTS EDUCATION FOR STRUCTURING CREATIVE ARTWORK: A SYSTEMATIC LITERATURE REVIEW - Siti Nur Farahie Buhari; Ahmad Johari Sihes (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This Systematic Literature Review (SLR) explores instructional strategies in visual arts education that promote structured creativity in student artwork, emphasizing methods that assist learners in expressing originality within defined frameworks. Visual arts education is essential for nurturing creative expression. However, educators often struggle to balance providing structured guidance and encouraging individual artistic exploration. To address this issue, a thorough search of scholarly articles was conducted using reputable databases, including Scopus and Web of Science, focusing on studies published between 2022 and 2024. The review process adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, resulting in 23 primary studies being analyzed. Findings were categorized into three main themes: (1) Creativity and Pedagogy in Visual Arts Education, (2) Innovative Approaches, and (3) Technological Integration in Visual Arts. The review indicates that incorporating structured instructional methods boosts students’ creative confidence, enabling them to pursue unique artistic expressions within supportive boundaries. The conclusion highlights the need for further research into adaptive instructional models suitable for various learning contexts in visual arts education. This synthesis provides educators with evidence-based strategies to enhance creativity within a structured artistic framework.